A modified basis of cubic B-spline with free parameter for linear second order boundary value problems: Application to engineering problems - Iqbal, Mudassar; Nooraini, Zainuddin; Hanita, Daud; Kanan, Ramani; Soomro, Hira; Rahimah, Jusoh; Ullah, Atta; Khan, Iliyas Karim (Elsevier Ltd, 2024)
The traditional cubic B-spline method offers limited local control over the curve solution. Adjusting the position of a control point affects the entire curve, making it challenging to make localized changes, e.g., smoothness. Moreover, the basis functions vanish on one side by the cubic B-spline method near the end conditions where the initial and boundary conditions are applied. To address these limitations, this research proposes a new basis by including a free parameter γ with the purpose of modifying the weights of nearby control points. This free parameter γ can influence the curve’s behavior in specific regions as well as the entire curve. This modification of the cubic B-spline method was used to approximate the second-order derivative at each collocation point. The convergence test showed that the proposed method was second-order convergent. Numerical examples of ordinary differential equations were used with different step values to evaluate the accuracy of the proposed method. The findings persistently indicated that the proposed technique provided better error estimates as compared to the other methods discussed in the literatures.